Manejo responsable de los desechos radiactivos en la Universidad de Costa Rica - Mora, Patricia (Universidad de Costa Rica, 2009)
The Radiation Safety Program (RSP) of the University of Costa Rica established in 1990, handles the radioactive waste generated at the University. A centralized storage waste room is used by the Atomic, Nuclear and Molecular Research Center, Health Research Institute, Molecular and Cellular Biology Research Center and the Environmental Contamination Research Center. The RSP has pre-storage procedures, internal controls, protocols for storage, withdrawal of sources and discharges to the environment, according to national and international legislation. The main radionuclides in liquid and solid wastes are P32, I125, S35 y C14; which after a storage period will be disposed of as exempted materials. The waste room also permanently stores sources with the following radionuclides Cs137, U238, Th232, Sr90, Ra226, Cd109, Cf252 and Am241. It has 96 permanent sources and 52 that will be disposed of. The RSP allows the University to have a centralized facility for the safe management of all radioactive waste generated locally.